Exploiting the Vacuum State in Materials with Plasmonic-to-Dielectric State Transition in Terahertz Gratings and Metasurfaces - Serebryannikov A.E.; Lakhtakia A.; Vandenbosch G.A.E. (My University, 2025)
Certain materials exhibit dynamically controllable transitions from the plasmonic state to the dielectric state, traversing through intermediate states. Components made of such materials disappear electromagnetically in the vacuum state, except for ohmic loss. We have demonstrated the use of two materials, InSb and graphene-dielectric metamaterial in reflection gratings, transmission gratings, and metasurfaces for on-off switching operations that rely on the vacuum state or somehow deviate from it. © 2019, META Conference. All rights reserved.